Integrating an Outcome-Based Education (OBE) Framework in Andragogy: A Case Study in the Community Education Department - Jubaidah Hasibuan; Friska Indria Nora Harahap (STAI Hubbulwathan Duri, 2024)
The challenges of 21st-century education include bridging the gap between higher education and the professional world through innovative learning approaches. Outcome-Based Education (OBE) aligns educational outcomes with the competencies required in public education professions. This study examines the planning, implementation, evaluation, challenges, and solutions related to OBE-based learning in Andragogy courses. A qualitative descriptive approach was employed, with 57 participants selected as the sample. Data were collected through observation, questionnaires, and document analysis. The planning process focuses on preparing learning tools and emphasizing the development of attitudes and skills aligned with teaching and community education administration professions. Learning begins with prayer and ice-breaking activities, followed by structured integration of OBE. No significant challenges were encountered in implementing the OBE framework, which was adapted to align with the expected learning outcomes of study programs. Students showed enthusiasm for the OBE model, which promotes innovative and engaging learning environments. The evaluation process utilized the PDCA (Plan-Do-Check-Act) cycle to identify areas for improvement and standardize effective methods. Continuous quality improvement (CQI) was achieved by revisiting the planning stage to refine the process. The integration of the OBE framework facilitates outcome-based learning, ensuring alignment with professional demands. The absence of major obstacles highlights the adaptability of OBE to enhance learning outcomes. The integration of the OBE framework in Andragogy courses, guided by the PDCA cycle, fosters continuous learning improvements and equips students with skills relevant to the professional world. This approach demonstrates the effectiveness of OBE in bridging education and work competencies.